The Media and Challenges of Promoting Democratic Governance in Nigeria - Zango, AbdulAziz Sani (Kashere Journal of Politics and International Relations, 2024)
Media is an essential component of democratic governance, this is because of the crucial roles it play in checking the excess of power abuse and influences public policies and programmes for the general well-being and interests of the electorates and the society. However, in Nigeria these roles have been impaired by number of challenges that combine to become bottleneck in their way of ensuring conduct of smooth democratic governance in the country. This paper examines the challenges facing media in promoting democratic governance in Nigeria. Library research is used as major methodology of the study. While, social responsibility theory is adopted as theoretical frame. It argues that if democratic governance is to be nurtured, maintained and consolidated, media must be accorded opportunities for providing plural avenues of channelling mass opinion and choices, and also serves as watch dog against the authoritarian tendencies. However, the paper discovers that firm government control, non-tolerance to opposition and financial consideration as well as ownership structure of the media, operational, technical and ethical problems have been identified as major obstacles toward the realization of their anticipated roles of promoting democratic governance. This ensures that the media is free from unnecessary governmental interference, corrupt free, free from engaging in primordial and parochial inclinations, technologically revolutionized, highly professionalized, ethically sound and bold, characterized by openness to all shades of opinions in the society.